Public Satisfaction And Quality Of Service Corner Driving License Forming Image Police - Indahingwati, Asmara (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
146 sampling research taking care of people who are driving license (SIM) in the police force aims to examine the relationship between service quality and satisfaction with the public image of the police institution. Data were collected through questionnaires and analyzed using the Likert model of multiple regression techniques. Results of hypothesis testing showed R = 0.619; F = 44.422; and p = 0.000 (p <0.05) showed that the quality of services and satisfaction of the people together influenced the image of the police. The coefficient of determination explains that the simultaneous quality of services and satisfaction of the people were able to contribute effectively to the image of the police amounted to 38.3%. The results of partial analysis shows that the relationship between service quality and image of the police has a value of p = 0.000 (p <5%), and r = 0.361, which means the quality of service to the image of the police institution is low. Partial assay analysis results between peoples satisfaction with the image of the police obtained value of p = 0.000 (p <0.05); r = 0.322, which means peoples satisfaction with the image of the police institutions have a significant positive correlation with the level of relationships is low